2020
DOI: 10.1016/j.cca.2020.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an automated chemiluminescence SARS-CoV-2 IG-G assay

Abstract: Highlights An extensive evaluation of the Abbott SARS-CoV-2 IgG assay. The assay shows excellent sensitivity/specificity with little cross-reactivity. Healthy volunteers and pre-pandemic samples had similar antibody cut-off indexes. A lower, optimised limit for reactivity improves sensitivity in early disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 25 publications
2
35
2
1
Order By: Relevance
“…In a study evaluating seven LFIAs [ 12 ], patients with lower IgM levels were more prone to produce borderline results on POCT testing; they found 6 asymptomatic RT-PCR positive COVID-19 patients who had repeated negative LFIA results. The sensitivities of the Architect and Cobas CLIAs are also different from our previous evaluations [ 1 , 2 ]. This is because the populations used in the previous studies were larger and had different demographics.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…In a study evaluating seven LFIAs [ 12 ], patients with lower IgM levels were more prone to produce borderline results on POCT testing; they found 6 asymptomatic RT-PCR positive COVID-19 patients who had repeated negative LFIA results. The sensitivities of the Architect and Cobas CLIAs are also different from our previous evaluations [ 1 , 2 ]. This is because the populations used in the previous studies were larger and had different demographics.…”
Section: Discussioncontrasting
confidence: 78%
“…CLIAs have the advantage in that they diagnose reactivity based on a reportable COI value. In our previous evaluation of the Abbott Architect IgG assay with a larger study population [ 1 ], an initial sensitivity of 45.9% within the first week of infection could be improved to 55.8% by using a lower, optimized COI value for reactivity. Other studies [ 24 ] have also suggested that a lower COI value for the diagnosis of reactive samples will improve the sensitivity of CLIAs in their cases with early infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations